Analisis Teknologi Chatbot Shopee dalam Meningkatkan Kepuasan Pengguna di Kota Pekalongan - Muhammad Malik Abdilah; Nabilla Septi Nur Alifah; Versiandika Yudha Pratama (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study aims to analyze user experiences when interacting with Shopee’s chatbot and to evaluate its contribution to user satisfaction in Pekalongan City. The research employed a qualitative approach with five informants selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using data reduction, data display, and conclusion drawing. The findings show that the chatbot provides users with convenience and fast access to basic information, helping them complete simple tasks more efficiently. However, the chatbot’s ability to understand the context of user questions remains limited, resulting in responses that are often general and not fully aligned with user needs. These limitations lead to varied levels of satisfaction depending on the complexity of the issues faced. The study concludes that Shopee’s chatbot has the potential to improve the quality of digital services if enhanced with better language comprehension and contextual understanding. The results highlight the need for further development of chatbot capabilities to create a more adaptive and satisfying service experience for users.